Tahsiin Mahaarat al-Istimaa’ Bistikhdaami Kahoot! Ladaa Thullaab al-Madrasat al-Tsanawiyyat Muhammadiyat al-Islamiyyat Solok Sumatra al-Gharbiyyat - Nisak, Amiratun; Hanomi, Hanomi; Asrina, Asrina (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
يهدف هذا البحث إلى تحديد نتائج التعلم لمهارات الاستماع لدى الطلاب قبل وبعد استخدام Kahoot!، وكذلك تقييم مدى فعالية استخدام Kahoot! حول مهارات الاستماع لدى طلاب الصف السابع بالمدرسة الثانوية محمدية الإسلامية سوليت أير سولوك سومطرى الغربية. يستخدم البحث تصميم بحث شبه تجريبي مع تصميم مجموعة ضابطة غير متكافئة. يتم تحديد نجاح الاختبار من خلال التقييمات القبلية والبعدية للاختبار. تكشف نتائج البحث أنه في الاختبار القبلي، حقق ما يقرب من 10% من الطلاب درجة قيمة المعيار الحد الأدنى ، بينما بعد استخدام Kahoot!، ارتفع هذا العدد إلى 76% أو أعلى، محققًا أو متجاوزًا درجة قيمة المعيار الحد الأدنى. يوضح هذا أن مهارات الاستماع لدى الطلاب تتحسن عند استخدام Kahoot! من خلال اختبار الفرضيات، تم تحديد مستوى الأهمية (Sig 2 tailed) ليكون 0.00، وهو أقل من 0.05. وبناء على ذلك، تم قبول فرضية هو، مما يشير إلى تأثير كبير لكاهوت! حول مهارات الاستماع لدى طلاب الصف السابع بالمدرسة الثانوية محمدية الإسلامية سوليت أير سولوك سومطرى الغربية. Abstract This research aims to determine the learning outcomes of students' listening skills before and after using Kahoot!, as well as to assess the effectiveness of using Kahoot! on the listening skills of class VII students at Muhammadiyah Islamic Middle School, Hard Air, Solok, West Sumatra. The research utilizes a quasi-experimental research design with a non-equivalent control group design. The success of the test is determined through pre-test and post-test evaluations. The research findings reveal that, in the pre-test, approximately 10% of students achieved the KKM score, whereas after using Kahoot!, this number increased to 76% or higher, meeting or surpassing the KKM score. This demonstrates that students' listening skills improve when utilizing Kahoot! Through hypothesis testing, the significance level (Sig 2 tailed) was determined to be 0.00, which is lower than 0.05. Accordingly, Ho's hypothesis is accepted, indicating a significant influence of Kahoot! on the listening skills of class VII students at Muhammadiyah Islamic Middle School, Hard Air, Solok, West Sumatra.